2018
DOI: 10.31788/rjc.2018.1144047
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Hydrophilic and Strong Pet-Based Membrane From Wasted Plastic Bottle

Abstract: In this study, the wasted plastic bottle has been recycled as a polymeric material to fabricate PET-based membrane by adding cellulose acetate and silica to enhance the performance. Cellulose acetate was added as a sub-polymer to increase mechanical property of the PET membrane. Meanwhile, silica which derived from rice husk was used as a membrane pore-forming agent. PET/CA/SiO2 membrane was fabricated using the phase inversion technique via thermal induced phase separation method. The permeation and selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…For F I G U R E 7 SEM images of the top surface of PET membranes 15% PET with solvent TFA/DCM 50/50, rejections around 75% for the corn starch were obtained, indicating, once again, the formation of defects or very large pores in the membrane structure. Comparing all the rejection results of this work with literature data, [17,19,20] it is reasonable to assume that the incorporation of additives, like PEG, PVP, and silica, could improve selectivity of the PET membranes since these additives led the membrane to have smaller pores.…”
Section: Filtration Experimentssupporting
confidence: 70%
See 2 more Smart Citations
“…For F I G U R E 7 SEM images of the top surface of PET membranes 15% PET with solvent TFA/DCM 50/50, rejections around 75% for the corn starch were obtained, indicating, once again, the formation of defects or very large pores in the membrane structure. Comparing all the rejection results of this work with literature data, [17,19,20] it is reasonable to assume that the incorporation of additives, like PEG, PVP, and silica, could improve selectivity of the PET membranes since these additives led the membrane to have smaller pores.…”
Section: Filtration Experimentssupporting
confidence: 70%
“…These values match a hydrophilic membrane surface, desirable for aqueous solution separations with hydrophobic solutes. [53][54][55] The hydrophilic character of the PET phase inversion membranes prepared in this work is an advantage compared to PET electrospun membranes À105 [56] and 134 [39] and hybrid PET/CA/silica phase inversion membranes -86 to 98 [20] found in the literature.…”
Section: Hydrophilicitymentioning
confidence: 92%
See 1 more Smart Citation
“…It was observed that the pore size and water permeability of the PET membrane were enhanced by using non-solvent of lower polarity and PEG with higher molecular weight and at higher concentration. PET-based membrane derived from phenol-dissolved waste PET bottles was also prepared through thermally induced phase separation (TIPS), with cellulose acetate as a sub-polymer to improve mechanical strength and rice husk-derived silica as a pore-forming agent [157]. The addition of 1 wt% silica improved the surface hydrophilicity and the distribution of pores on the membrane surface, hence resulting in two-fold increment in its water permeability compared to that without silica additive.…”
Section: Polymers and Plasticsmentioning
confidence: 99%
“…The phase inversion process is the most popular method for membrane fabrication due to its simplicity and ability to produce variable membrane types and properties [1]. Some polymers widely used for membrane fabrications are polyvinylidene fluoride (PVDF), polyethersulfone (PES), polysulfone (PSF), and polyacrylonitrile (PAN) [2,3,4]. Among these polymers, PVDF offers the advantages of having good mechanical properties, good thermal stability, and excellent chemical resistance [2,5,6,7,8,9,10].…”
Section: Introductionmentioning
confidence: 99%